ANALYZE THE IMPACT OF LEARNING PRONOUNS IN IMPROVING LEARNERS' LANGUAGE SKILLS - Princess Sakinah; Irawati Tarihoran; Raja Nazira Tasya Fadillah; Syahida Az Zahra; Yani Lubis (PT. Intelek Cendikiawan Nusantara, 2024)
The problems faced by students of North Sumatra State Islamic University in the use of pronouns and their application in improving the language of students. This study aims to determine the understanding of students in using appropriate pronouns and the problems that hinder them in learning can be seen from their lack of proficiency in applying pronouns in language both in writing and orally. Observation method was used in this research. This study uses data collection techniques. The research used is an interview test. From the test that took place, it was analyzed to measure the average knowledge in the application of pronouns. Pronouns are parts of speech which we can interpret as “pronouns”. The function of pronouns themselves is very important to learn in order to replace nouns such as people, objects, animals, and other things that are abstract. Another reason for learning pronouns is to avoid repeating the use of nouns which by nature are not needed. Based on the results of this study, it can be concluded that students often have problems in using pronouns. This is due to some of them who are not fluent in mastering pronoun learning and English that is not mastered by them. Driven by low learning factors, and not getting enough examples, practice, and often not having guidance from their English teachers who are proficient in the field therefore it needs to be realized as early as possible so that as learners are more active again in mastering the material in order to minimize the lack of understanding of planning.